TRADITIONAL VS. PAIRED SERIES AGONIST-ANTAGONIST METHOD FOR LOWER LIMBS: ARE THERE DIFFERENCES IN TOTAL VOLUME AND MAXIMUM REPETITIONS? - Tozei, William Peneda (2021)
The objective was to compare the total volume and number of maximum repetitions (nMR) that can be performed in Leg Extensions (EXT) and Leg Flexion (FLEX), varying order of execution in traditional (TRAD) and agonist-antagonist paired set (AAPS) methods. Total volume and nMR of twelve men (22.8±2.7years) were evaluated (p<0.05) in four protocols: TRAD1 (4 sets EXT + 4 sets FLEX); TRAD2 (4 sets FLEX + 4 sets EXT); AAPS1 (4 sets EXT and FLEX) and; AAPS2 (4 sets FLEX and EXT). The total volume of the AAPS2 was greater than TRAD1 and TRAD2. Higher nMR was observed in FLEX compared to EXT in all protocols. It was concluded that depending on the method chosen and order of exercises, a greater total volume can be performed. Additionally, the nMR that can be performed in each resistance exercise seems to be influenced by the muscle group.